Peningkatan Pendapatan Petani Pertanian Terpadu Ternak Sapi Perah Dan Kelapa Sawit Di Kabupaten Pelalawan Provinsi Riau - Siswati, Latifa; Rizal, M (Fakultas Peternakan Universitas Jambi, 2017)
The aim of this study was to reveal the increase of farmer family income at oil palm plantation and dairy farm in supporting the comodity of plantation in Indonesia especially Riau Province. Survey method was applied in this study in which the samples were collected as the purposive sampling. Result of the experiment showed that integratiob system of raising cow within oil palm plantation might have a good petency in supporting the development of the oil palm plantation. Cows would provide organc fertilizer and improve the soil tecture and this integration system could reduce the production cost. Selection of farmer could be based on location determination, program socialisation, participative plan, development activity and evaluation of program. This program could contribute to the farmer income that could be an alternative side income especially during low oil palm price. The farmer income was around Rp 3.600.000 ha-1 farmer-1 from at oil palm plantation and Rp 4.819,500,- month-1 farmer-1. The total farmer income was around Rp 8.419,500,-